Comparative Anti-microbial activity and brine shrimp lethality bioassay of different parts of the plant Moringa oleifera lam - Kaniz Fatima Urmi, Nurul Huda Md. Masum, Abu Hasanat Md. Zulfiker, Md. Kamal Hossain and Kaiser Hamid (Journal of Applied Pharmaceutical Science)
The aim of the present study was to determine the antimicrobial and cytotoxic activity of different parts of the plant Moringa oleifera Lam. Disc diffusion method and brine shrimp lethality bioassay were used for antimicrobial activity and cytotoxic activity respectively. Chloroform fractions of leaf and fruit part have shown moderate antimicrobial activity with zone of inhibition (ZOI) ranging from 9-28 mm against all the experimental microbes. Ethyl acetate fraction of bark and fruit found to have highest antimicrobial activity with zone of inhibition (ZOI) 36 mm against Shigella dysphoria. Pet ether fraction of bark but not leaf showed activity against Bacillus megaterium. Pet ether fraction of bark showed highest activity against Candida albicans with zone of inhibition (ZOI) of 35 mm while chloroform fraction of the leaf showed highest activity against Bacillus megaterium with zone of inhibition (ZOI) of 25 mm. All the fractions were found to have potential cytotoxic activity having LC50 values ranging from 0.43-1.18 µg/ml in comparison with vincristine sulphate having LC50 value of 0.53 µg/ml. Ethyl acetate fraction of fruit showed highest cytotoxic activity with LC50 value of 0.43 µg/ml while pet ether fraction of bark showed lowest cytotoxic activity with LC50 value of 1.18 µg/ml.
Keywords: Moringa oleifera, antimicrobial, cytotoxic, zone of inhibition.